2002
DOI: 10.1038/sj.bmt.1703315
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage following bone marrow transplantation: an autopsy study of 58 patients

Abstract: Summary:Autopsy files of 180 patients were reviewed, who died after BMT between July 1987 and June 1998 and 58 (32.2%) cases, who had experienced intracranial hemorrhage (ICH) were selected. Age, sex, underlying disease, preparatory regimens, immunoprophylaxis, chronic and acute GVHD, survival of the patients and localization and size of hemorrhages were evaluated. There were 33 males and 25 females, with a mean age of 23.4 years. The main underlying disorders for which BMT was performed included SAA (n = 21),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…In 2002 Bleggi-torres et al examined the results of 58 autopsies of patients who had received hsct and had developed intracranial hemorrhage 18 . the authors reported that 40 patients had intracerebral hemorrhage, 35 subarachnoid hemorrhage and eight subdural hemorrhage 14 . In 16 cases bleeding was extensive and directly related to death 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2002 Bleggi-torres et al examined the results of 58 autopsies of patients who had received hsct and had developed intracranial hemorrhage 18 . the authors reported that 40 patients had intracerebral hemorrhage, 35 subarachnoid hemorrhage and eight subdural hemorrhage 14 . In 16 cases bleeding was extensive and directly related to death 14 .…”
Section: Discussionmentioning
confidence: 99%
“…the authors reported that 40 patients had intracerebral hemorrhage, 35 subarachnoid hemorrhage and eight subdural hemorrhage 14 . In 16 cases bleeding was extensive and directly related to death 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, specialized clinical programs, such as hematopoietic stem cell transplantation (HSCT), are evolving rapidly and rely on strict quality control and feedback mechanisms to improve clinical outcomes. Moreover, autopsy series have been instructive in understanding patterns of graft-versushost disease (GVHD), 9 as well as infectious, 10 and toxic complications [11][12][13] of HSCT. Rates of post-mortem exams at bone marrow transplant centers, however, have not been specifically documented.…”
mentioning
confidence: 99%
“…Intracranial bleeding has also been reported in children treated with radiation therapy [2]. Hemorrhage may occur in a variety of locations, i.e., subdural, subarachnoid, and intracerebral [23]. Almost one-fifth of patients have more than one type of hemorrhage.…”
Section: Hemorrhagic Complicationsmentioning
confidence: 96%
“…Prolonged thrombocytopenia leads to catastrophic and fatal cerebral hemorrhage [22,23]. It can be explained by a chemotherapy or radiation-induced decrease in megakaryocytes, or alternatively by immunological (autoimmune) or drug-induced mechanisms of platelet destruction or dysfunction, particularly L-asparaginase.…”
Section: Hemorrhagic Complicationsmentioning
confidence: 99%